Morphometric Evaluation of the Hip Joint in Dogs - Kacková Gabriela; Horňák Slavomír; Figurová Mária; Vargová Nela; Tauberová Veronika (Folia Veterinaria)
Hip dysplasia represents the most prevalent non-traumatic disease leading to lameness in dogs, which subsequently causes secondary joint pathologies such as arthrosis and arthritis. Diagnosis and selection for breeding use radiographic evaluation of the ventrodorsal projection of the hip joint. Early detection and treatment can halt or reverse the disease progression. In veterinary medicine, various radiological measurements are applied to evaluate such anatomical abnormalities. These measurements include the Norberg angle, percentage coverage of the femoral head, and various indices related to the acetabulum and proximal femur. The differences in measurements between breeds are significant and reflect differences in body conformation. Ventrodorsal radiographs are crucial for the diagnosis, screening and monitoring of hip dysplasia. Lack of reference values for morphometric measurements in dogs highlights the need for further research.